Analisis Hidrogeologi untuk Rencana Sistem Penyaliran di Pit S22GN Penambangan Batubara Tahun 2018 PT. Riung Mitra Lestari Jobsite PT. Kitadin, Desa Embalut, Kecamatan Tenggarong Seberang, Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur - Jessy Syarastika; Tamrin Kasim (Journals Mining Engineering : Bina Tambang, 2018)
One of PT Riung Mitra Lestari site mines is pit S22GN. Pit S22GN has 20,8 Ha of areas that operated since January 2018. In location, it observed many puddle of surface water that can disturb front and coal haulling . This is caused by mine drainage unfully set by company and flat topography so water is difficult to flows. Beside that, a wide catchment area is very potentially create so much run off. Groundwater observed participated to become a total runoff so it should be analyzed. Plan of precipitation based on data 2008 – 2017 shows that in 2018 rainfall will be maximum in 98,96 mm/day, so it effected to intensity of rain fall in catchment area 1 is 3,88 mm/hour and catchment 2 is 4,87 mm/jam in 2 years of cycle periods. Calculation result shows, in catchment 1 produces 3636 m3/hour  of runoff and 131,017 m3/hour of groundwater  that flows to the front, and in catchment area 2 produces 1927,6 m3/hour  flows to minedout area. It designed 2 kinds of sump (main sump and temporary sump) and 2 kinds of open channel with trapezium shapes of cross section. Water flows helped by 2 kinds of VolvoKSBLCC-H 200-610 pumps with HDPE piping. And at last, settling pond designed become 5 compartement with 1313,424 m3 of capacity each one. Keyword: Mine Drainage, Hydrogeological Analysis, Sump, Open Channel, Settling Pond